The Effectiveness of Instrumental Music Therapy and Self-Hypnosis on Decreasing Blood Pressure Level among Hypertension Patients - Edi Purnomo; Akbar Nur; Rachmawati Rahim; Zulhaini Sartika A. Pulungan (Alta Dharma Publisher, 2020)
Heart and blood vessel disease, including hypertension, are the highest cause of death in the world. Instrumental music and self-hypnosis are choices to achieve a relaxed state and cause stable blood pressure. The study aimed to determine the effectiveness of instrumental music and self-hypnosis therapy to decrease the blood pressure of hypertensive patients. This study employed a quasi experimental design, pre-test and post-test with non-equivalent control group Forty-six patients were recruited and allocated in the experimental group and the control group. The experimental group received the standard pharmacological therapy and combination instrumental music and self-hypnosis therapy. While the control group received the standard pharmacological therapy. Data were analyzed using a paired t-test and independent sample t-test. The results showed significant decrease in systolic blood pressure after instrumental music and self-hypnosis therapy (p = 0.001) and a significant decrease in diastolic blood pressure after the administration instrumental music and self-hypnosis therapy (p = 0.005). Researchers recommend the use of instrumental music and self-hypnosis therapy to reduce the blood pressure of hypertensive patients